Designing Performance Measurement Instrument With Balance Scorecard Framework And Ahp Method (case Study At Pt. Bina Karya Persero) - Riandi Aditia Darmayana; Budi Sulistyo; Atya Nur Aisha (eProceedings of Engineering, 2018)
Abstract: PT Bina Karya Persero is a company's State-Owned Enterprise (SOE) engaged in the field of multidisciplinary engineering and consultancy management. The company currently has implemented â€œKriteria Penilaian Kinerja Unggulâ€ (KPKU) to measure their performance that tends to be too general and not necessarily in line with the companyâ€™s goals. KPKU based on this measurement, the financial performance of the company experienced a fluctuation financial target have not been achieved. Therefore, this study aimed to design a performance measurement system using BSC method focusing on Financial Perspective, Customer Perspective, Internal Business Process Perspective, and Learning and Growth Perspective. The result showed that there are nine strategies, 13 strategic objectives, and 19 Key Performance Indicators (KPI). After implementing the weight for each BSCâ€™s criteria, the Financial Perspectives made 30% of all criteria. Meanwhile the weight of the Customer Perspective is 21%, the weight of Internal Business Process Perspective is 29% and the weight of Learning and Growth Perspective is 20%. The BSC designed in this study should be implemented in the following year to improve the companyâ€™s performances. Keywords: Balanced Scorecard (BSC), Key Performance Indicator, State-owned enterprises (SOEs), Analytical Hierarchy Process (AHP) Keywords: Balanced Scorecard, Performance, SWOT, Strategy Map, KPI, AHP